An evaluation of lucerne varieties suitable for different agro-ecological zones in Kenya - Lukuyu, Ben A.; Methu, J.N.; Mwangi, D.; Kirui, Josephine; Mwendia, Solomon W.; Wamalwa, J.; Kavatha, A.; Ngae, G.N.; Mbure, G.N. (Springer, 2011)
In order to choose suitable varieties with high yield and good quality for cultivation, eight lucerne varieties, including seven foreign ones (WL 625 HQ, KKS 9595, WL 414, Robusta, KKS 3864, SA Standard, WL 525 HQ), and a local check Hunter River were studied on farm in seven different agroecological zones (AEZ) in the long and short rain seasons in 2006 using a randomized block design with two replications. Each plot was cut two times in both seasons to evaluate herbage production of the tested varieties. Results showed that dry matter yield (DM) from varieties was significantly different between sites in both short (P <0.05) and long (P < 0.001) rains seasons. Robusta and WL 525 HQ yielded significantly (P < 0.05) more DM compared to the local check Hunter River in both wet mid- and highland zones while SA Standard yielded significantly (P < 0.001) more DM in high dry land zones across all seasons. There was a significant AEZ × variety interaction on leaf:stem ratio in both short (P < 0.001) and long (P < 0.05) rains seasons. In both rain seasons, WL 414, WL 625 HQ and KKS 3864 had significantly (P < 0.05) higher leaf:stem ratio in that order to the local check Hunter River across all zones. Similarly, in both rain seasons, age at harvested significantly affected DM yield (P < 0.05) and leaf:stem ratio (P < 0.005) of all varieties across all zones.